Physical activity attenuates the effect of the FTO genotype on obesity traits in European adults: The Food4Me study. Issue 4 (27th February 2016) - Celis‐Morales, Carlos; Marsaux, Cyril F.M.; Livingstone, Katherine M.; Navas‐Carretero, Santiago; San‐Cristobal, Rodrigo; O'donovan, Clare B.; Forster, Hannah; Woolhead, Clara; Fallaize, Rosalind; Macready, Anna L.; Kolossa, Silvia; Hallmann, Jacqueline; et al.
Abstract : Objective: To examine whether the effect of FTO loci on obesity‐related traits could be modified by physical activity (PA) levels in European adults. Methods: Of 1, 607 Food4Me participants randomized, 1, 280 were genotyped for FTO (rs9939609) and had available PA data. PA was measured objectively using accelerometers (TracmorD, Philips), whereas anthropometric measures [BMI and waist circumference (WC)] were self‐reported via the Internet. Results: FTO genotype was associated with a higher body weight [ β : 1.09 kg per risk allele, (95% CI: 0.14‐2.04), P  = 0.024], BMI [ β : 0.54 kg m −2, (0.23‐0.83), P  < 0.0001], and WC [ β : 1.07 cm, (0.24‐1.90), P  = 0.011]. Moderate‐equivalent PA attenuated the effect of FTO on BMI ( P [interaction]  = 0.020). Among inactive individuals, FTO increased BMI by 1.06 kg m −2 per allele ( P  = 0.024), whereas the increase in BMI was substantially attenuated among active individuals (0.16 kg m −2, P  = 0.388). We observed similar effects for WC ( P [interaction]  = 0.005): the FTO risk allele increased WC by 2.72 cm per allele among inactive individuals but by only 0.49 cm in active individuals. Conclusions: PA attenuates the effect of FTO genotype on BMI and WC. This may have important public health implications because genetic susceptibility to obesity in the presence of FTO variants may be reduced by adopting a physically active lifestyle.